Rural America In the Information Age: Telecommunications Policy for Rural Development; and The Writer's Friend - Robert G. Hays (Journal of Applied Communications, 1990)
Review of "Rural America In the Information Age: Telecommunications Policy for Rural Development" by Edwin B. Parker, Heather E. Hudson, Don A. Dillman, and Andrew D. Roscoe; and "The Writer's Friend," by Martin L. Gibson.